She/he/they/them : understanding gender identity - Stanborough, Rebecca (Informed! (North Mankato, Minn.), 2020)
Explores the different issues surrounding gender identity, including what it is, different types of genders, gender expression, how society shapes gender norms, and gender equity. Includes tips for getting involved, discussion questions, a glossary, and resources for further information.